2021
DOI: 10.1111/apps.12360
|View full text |Cite
|
Sign up to set email alerts
|

Understanding “Zoom fatigue”: A mixed‐method approach

Abstract: Video conference meetings, which became frequent during the COVID‐19 pandemic, might result in exhaustion (so‐called “Zoom fatigue”). However, only little is known about “Zoom fatigue,” the objective characteristics shaping it, and the subjective experiences eliciting this phenomenon. Gaining this knowledge is critical for understanding work life during the pandemic. Study 1, a within‐person quantitative investigation, tested whether video conferences are exhausting and if objective characteristics (i.e. meeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(93 citation statements)
references
References 71 publications
2
84
0
7
Order By: Relevance
“…Hence, apart from aforementioned general dispositions, there are VC-specific individual factors such as mental and physical health and fitness, stress management skills and VC skills that influence the individual’s susceptibility for experiencing exhaustion and fatigue in relation to VC. Qualitative data indicate that negative versus positive attitudes towards VC influence susceptibility to VC fatigue [ 34 ]. Further, the survey study by Oducado et al [ 30 ] found that negative attitudes towards VC go hand in hand with higher reported levels of fatigue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, apart from aforementioned general dispositions, there are VC-specific individual factors such as mental and physical health and fitness, stress management skills and VC skills that influence the individual’s susceptibility for experiencing exhaustion and fatigue in relation to VC. Qualitative data indicate that negative versus positive attitudes towards VC influence susceptibility to VC fatigue [ 34 ]. Further, the survey study by Oducado et al [ 30 ] found that negative attitudes towards VC go hand in hand with higher reported levels of fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…Number and Duration of VC Sessions: Several studies have reported that the increased number (and in some cases also increased length) of VC meetings can be linked to VC fatigue [ 15 , 29 , 30 , 47 , 54 ]. The study presented in [ 34 ], however, suggested that the perceived duration of a meeting may be a more relevant factor than the meeting duration per se, thus indicating the need for follow-up studies. Further, earlier work in the field of meeting science has shown that the number of meetings and meeting load have a negative impact on employee well-being and are associated with higher daily fatigue and subjective workload [ 45 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…This shift illustrates the increasing use of online platforms by citizens, which many of us became accustomed to by October 2020, the end of phase 2. By this time, phrases like ‘Zoom fatigue’ had already begun to creep into our ‘new normal’ vernacular [ 13 ]. It is worth noting that although during a short period of easing restrictions in the summer of 2020 (covered in Phase 2), this trend was still shaping and growing.…”
Section: Discussionmentioning
confidence: 99%
“…One widespread behavioural change many experienced throughout the pandemic has been the necessity to incorporate the use of online platforms to engage in activities remotely where one would previously have engaged in-person. An example of this is the use of Zoom to attend work meetings or to spend time with loved ones [ 13 ]. While some can seamlessly shift pastimes and livelihoods from in-person to online, other individuals may have ceased activities altogether or engaged in completely new pastimes.…”
Section: Introductionmentioning
confidence: 99%
“…While one study found no performance differences in a multisensory motion perception task when comparing a virtual with an in-person setting 15 , another study demonstrated that transmission delays during video conferencing disrupt the natural rhythm of a conversation, leading to delays in turn initiation 16 . Potentially related, there is both anecdotal and empirical evidence that prolonged virtual interactions lead to feelings of exhaustion and irritation, a mental state commonly referred to as "Zoom ® fatigue" [17][18][19][20][21] . Researchers demonstrated that frequency, duration, and time between video conferencing were associated with a higher level of fatigue.…”
Section: Introductionmentioning
confidence: 99%